Voices of the American past - Raymond M. Hyser; J. Chris Arndt (Thomson Wadsworth, 2008)
VOICES OF THE AMERICAN PAST is a two-volume reader that presents a variety of diverse perspectives through more than 230 primary sources. Excerpts from speeches, letters, journals, magazine articles, hearings and government documents raise issues from both public and private aspects of American life throughout history. A "Guide to Reading and Interpreting Documents" in the front matter explains how and why historians use primary source evidence, and outlines basic points to help students learn to analyze sources. Brief headnotes set each source into context. "Questions to Consider" precede each document, offering prompts for critical thinking and reflection. The volumes are organized chronologically into 31 chapters, with the Reconstruction chapter overlapping in both volumes -- corresponding to the splits of most survey texts.